PENGARUH TOTAL ASSET TURNOVER DAN UKURAN PERUSAHAAN TERHADAP PERTUMBUHAN LABA PADA PT. INDOCEMENT TUNGGAL PRAKASA TBK PERIODE 2014-2023 - Aditya Pratama, Rizki; Syakhrial Syakhrial (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the effect of Total Asset Turnover and company size on profit growth at PT Indocement Tunggal Prakasa Tbk for the period 2014-2023. The method used is quantitative. The sample in the study is to determine annual data collection starting from 2014 to 2023. Data analysis uses IBM SPSS Statistics with multiple linear regression methods. The results of the analysis showed that Total Asset Turnover obtained a t-value of 13.876> t-table 2.365 and obtained a sig value of 0.000 <0.05, meaning that Total Asset Turnover has a positive and significant effect on profit growth. Company size obtained a t-value of 1.289 <t-table 2.365 and obtained a sig value of 0.615> 0.05, meaning that company size has no effect on profit growth. Total Asset Turnover and company size obtained an Fcount value of 403.189 > FTable 4.07. This is reinforced by a significance probability of 0.000 < 0.05, meaning that Total Asset Turnover and company size simultaneously influence profit growth. R-Square of 0.427 means that the influence of Company Size and Total Asset Turnover on Profit Growth is 42.7%.